EVALUATION OF USE THE PREDICTIVE MODEL FOR THE COMPLICATED COURSE OF SUPRAVESICAL OBSTRUCTION IN PREGNANCY IN CHOICE OF TREATMENT TACTICS - Khasanov, M.M. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
To identify the cut-off values for the model of predicting the course of complicated supravesical obstruction in pregnant women (PCCSOP) when choosing treatment tactics. Materials and methods: In a prospective study, data from 405 pregnant women were analyzed, in each case, Z values of the PCCSOP model were noted, and the treatment tactics were chosen as the outcome. Results: the Z value for the control group mean was 2.88±0.87 (2.71-3.21), for the outpatient group, which included 51 patients without AB, mean was 4.55±1.27 (2.71-3.21), for the outpatient group, 125 patients who received AB therapy mean was 5.21±1.22 (3.4-6.14). The values of Z in the group of 108 patients with inpatient treatment mean was 6.58±1.11 (5.22-7.98). In the group of 84 patients who received surgical treatment mean Z value was 9.44±1.57 (9.11-11.02). The ROC curve analysis data showed that the cut-off values for the group of outpatient patients without antibiotic therapy were 3.55, for the out-patient group with AB therapy – 5.94, for the inpatient group – 7.42 and for surgical treatment – 9.55. Conclusion: The PCCSOP model, which is characterized by high sensitivity and specificity, makes it possible to classify pregnant women not only for the presence of a complicated course but also, based on the value of the model, to determine the tactics of treatment of pregnant women with supravesical obstruction.